Assessing Seasonal Variations of Vegetation Cover Using NDVI in Context Climate Change in Wasit - Mohanad I. Khalbas; Jasim H. Kadhum (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
This study assesses and analyzes the annual and seasonal changes in the Normalized Difference Vegetation Index (NDVI) in Wasit Province, Iraq, between 2020 and 2023. Vegetation cover (VC) variation serves as a key indicator of climate change impacts on ecosystems and agricultural productivity. The research employs satellite-derived NDVI and climate data to detect spatiotemporal changes across the region. Geographically, the Tigris River divides Wasit into two zones: the southern and southwestern parts exhibit higher NDVI values due to abundant water from river branches, whereas the northern and northeastern areas show lower values. A slight improvement in VC was observed in December 2020, likely due to increased Tigris River discharges. Findings indicate a gradual NDVI increase over the study period, with the highest value recorded during summer 2023 (2.94%), highlighting the role of irrigation and modern agricultural practices in enhancing VC beyond the influence of climate factors. Seasonal variations were evident, with summer NDVI values generally exceeding those in winter; the highest winter NDVI was in 2021 (2.40%). Three statistical methods were applied: correlation analysis, linear regression, and ANOVA. Results showed a weak negative correlation between NDVI and precipitation (r = -0.60), and a negligible correlation with air temperature (r = 0.06). ANOVA confirmed significant differences in NDVI values across the years (p = 0.0039), indicating real ecological changes rather than random variation. Using the ARIMA model for forecasting, NDVI is expected to continue a slight upward trend, reaching 0.442 in 2024 and 0.463 in 2025. This suggests a positive vegetation response driven more by improved agricultural and water management practices than by climatic changes.